Peran Pola Asuh Orang Tua dalam Perilaku Melanggar Peraturan di Pondok Pesantren Sunan Drajat Asrama Al-Khodijah - Selly Silvia (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2022)
Family is the first thing that affects a child's education. The family is a powerful institution that stands in all corners of the world. The family is the place where humans are first educated and trained to navigate their lives. The first environment known to children is family, especially parents, children will imitate everything their parents do, starting from language, speaking style, behavior, including solving problems. Because parents are the first teachers for their children, the role of parents is very important for children, especially in children's behavior. This research approach uses a descriptive approach to the type of qualitative research. This approach was taken because in this research it seeks to examine social phenomena in a natural setting, not in controlled or laboratory conditions. Bogdan and Taylor, define a qualitative approach as a research procedure in the form of written or spoken words from people and observed behavior. The results of the study Parenting patterns are very influential in the behavior of female students. The better the parenting applied, the better the behavior of the female students. the behavior of female students in addition to parenting is parental control of children in boarding schools. If the parenting provided by parents is getting better, the child's aggressive behavior will be lower. Likewise, if the parenting provided by parents is not good, the aggressive behavior of children will also increase. But it would be better if it was balanced with parental control.